OP34 Enteral Nutrition Compared with Steroids in Children with Crohn's Disease – In Israel: a nationwide study from the epi-IIRN. (30th January 2023) - Plotkin, L; Lujan, R; Focht, G; Greenfeld, S; Loewenberg Weisband, Y; Lederman, N; Matz, E; Dotan, I; Turner, D
Abstract: Background: Studies have shown that exclusive enteral nutrition (EEN) treatment is as effective to corticosteroids (CS) for induction of remission in pediatric Crohn's disease (CD) with fewer side effects, but long-term outcome data are scarce. In this nationwide study we aimed to compare the risk of complicated disease course (CDC) after 2 years of follow-up in children with CD receiving EEN or CS as induction therapy. Methods: Data of children diagnosed with CD in the epi-IIRN cohort between 2005-2020 were retrieved from the 4 Israeli Health-Maintenance-Organizations covering 98% of the population. The primary outcome was CDC defined as CD-related surgery, steroid-dependency, or need for more than one biologic class during 2 years post-diagnosis. Secondary outcomes included hospitalizations, and the use of biologics (any). Additionally, anthropometrics, labs reflecting nutrition (i.e., Alb and HGB), and growth were assessed at repeated visits until 2 years thereafter. To account for confounding by indication bias, we compared children with similar baseline characteristics based on Propensity Score (PS) individual matching. Time to CDC outcome was evaluated using Kaplan-Meier survival curves and compared by the log-rank test. A Cox proportional hazard model was sought to assess the relationship between the type of induction and time to CDC outcome. Results: A total of 785 children with CD were induced after diagnosis with either EEN (n=410) or CS (n=375); mean age 13.3±3.5 years, 59% males. PS successfully matched 116 pairs of whom 85 (36%) had CDC. The survival probability of CDC at 6, 12, 18, and 24 months was higher in the CS group compared to the EEN group at all time points (5%vs4%, 12% vs 10%, 22% vs 3%, and 27% vs.16%, respectively p=0.045; fig. 1). In a Cox multivariable model adjusted by year of diagnosis, CS induction treatment was similarly associated with higher hazard of CDC by 2 years (HR 1.8 [95%CI 1.01-3.25]). The survival probability of hospitalization was also higher in the CS group at 6, 12, 8, and 24 months (16% vs 9%, 20% vs 12%, 25% vs 14%, and 27% vs. 15%, respectively, p=0.024; fig.2). There was no difference in time to biologics (p=0.96, n=59 (51%) in EEN, n=57 (49%) in CS) and anthropometric data (Table 1). Significant improvements were observed in HGB and Alb levels for the EEN group during the first 3 months from diagnosis compared with the CS (p=0.046 and p=0.035 respectively) (table 1). Conclusion: EEN as induction therapy in pediatric CD is associated with a lower long-term risk of complicated disease course and larger improvement in HGB and Alb but not in growth parameters compared with CS, even when adjusting to baseline disease severity and patients characteristics.